Simplified Modular Access to Enantiopure 1,2-Aminoalcohols via Ni-Electrocatalytic Decarboxylative Arylation - Sun, Jiawei; Endo, Hirofumi; Emmanuel, Megan A.; Oderinde, Martins S.; Kawamata, Yu; Baran, Phil S. (Journal of the American Chemical Society, 2024)
Chiral aminoalcohols are omnipresent in bioactive compounds. Conventional strategies to access this motif involve multiple-step reactions to install the requisite functionalities stereoselectively using conventional polar bond analysis. This study reveals that a simple chiral oxazolidine-based carboxylic acid can be readily transformed to substituted chiral aminoalcohols with high stereochemical control by Ni-electrocatalytic decarboxylative arylation. This general, robust, and scalable coupling can be used to synthesize a variety of medicinally important compounds, avoiding protecting and functional group manipulations, thereby dramatically simplifying their preparation.